ANALISIS MOTIVASI BELAJAR SISWA MELALUI PERTUNJUKAN SENI TARI PADA SISWA KELAS V SD NEGERI 107417 SEI MERAH - Dwi Putri Dina Saharani Putri; Putra Afriadi; Laurensia Masri Perangin Angin; Sri Mustika Aulia; Waliyul Maulana Siregar (STKIP Subang, 2025)
This study aims to investigate students’ learning motivation through dance performances in Grade V at SD Negeri 107417 Sei Merah. The background of this research is the low learning motivation among students, indicated by a lack of participation and enthusiasm during lessons, especially in dance classes. This study employed a descriptive quantitative method using purposive sampling. The sample consisted of 1 teacher and 12 fifth-grade students. Data were collected through observation, interviews, documentation, and a questionnaire consisting of 20 statement items. The data were analyzed using descriptive statistical techniques in the form of percentages. The results showed that students’ learning motivation was categorized as